Physicomechanical and cellular behavior of 3D printed polycaprolactone/poly(lactic‐co‐glycolic acid) scaffold containing polyhedral oligomeric silsesquioxane and extracellular matrix nanoparticles for cartilage tissue engineering. (2nd June 2022) - Alidadi Shamsabadi, Zahra; Mahdavi, Hamid; Shojaei, Shahrokh; Salehi, Hossien; Valiani, Ali
Abstract: The common disease of articular cartilage is osteoarthritis, which can be diagnosed with the degradation of the articular cartilage a well as formation of osteophytes, subchondral sclerosis, synovial inflammation and ultimate loss of joint function. Due to the lack of articular cartilage regeneration as well as shortage of appropriate treatment, tissue engineering has been widely used to fabricate hybrid scaffolds for supporting cartilage tissue regeneration using 3D fabrication and design techniques. In this study a 3D scaffold was designed using polycaprolactone (PCL)/poly(lactic‐co‐glycolic acid) (PLGA) biomaterial inks. Moreover, in order to achieve mechanical consistency and optimize the printing process, different concentrations of polyhedral oligomeric silsesquioxane (POSS) nanoparticles including 0, 3 and 5 (% w/v) were added. The cartilage derived extracellular matrix (ECM) particles were used as the filler to improve hydrophilicity, optimal porosity formation, optimal mechanical properties and print resolution. The samples were evaluated in terms of morphology, thermal properties, physicochemical structure, hydrophilicity, mechanical properties, biodegradation as well as thermal and cell culture study. Results showed that the compressive modulus of the PCL/PLGA/20%ECM/3%POSS 3D printed scaffolds was higher than other scaffolds. By adding 20% (w/w) ECM to the basic biomaterial ink viscosity of the biomaterial ink, porosity and water uptake were increased significantly. The 3D printed scaffold containing PCL/PLGA/5%POSS/20%ECM components demonstrated high biocompatibility as well as cell viability. Therefore, it was concluded that 3% POSS accompanying 20% ECM addition was the most suitable bioink composition for fabricating the most biocompatible and applicable scaffold for cartilage tissue engineering applications.